Shifts in the Bacterial Community Related to Quality Properties of Vacuum-Packaged Peeled Potatoes during Storage - Zudi Li (Foods, 2022)
To reveal the potential relationship between the bacterial community and quality attributes of vacuum-packaged peeled potatoes, the bacterial community dynamics, visual quality, organic acids, flavor and volatile organic compounds (VOCs) during 12 days of storage under 10 °C were studied, and a correlation analysis was performed between the bacterial community and VOCs. During the whole storage, the dominant bacteria changed from Ralstonia, Pseudomonas, Pantoea and Comamonas to Clostridia, Clostridium, Lacrimispora, Lactococcus and Leuconostoc. The visual quality and hardness deteriorated significantly on day 12; meanwhile, lactic and acetic acid content accumulated to 0.79 and 4.87 mg/g FW, respectively. Potatoes’ flavor deteriorated severely after 8 days, as evidenced by results of an electronic nose (e-nose). A total of 37 VOCs were detected, and the total content showed an increasing trend from 2164.85 to 10658.68 μg/kg during the whole storage. A correlation analysis showed that Enterobacteriaceae, Erwinia, Lacrimispora, Lactococcus, Serratia, Pantoea, Clostridium, Flavobacterium and Clostridia were positively correlated with the biosynthesis of VOCs. In addition, 10 spoilage markers were screened according to a variable importance in projection (VIP) ≥ 1. Ethanol, which was the most abundant spoilage marker, was significantly related to Enterobacteriaceae, Erwinia, Lacrimispora and Lactococcus. The results of this study have great practical significance for prolonging the shelf life of fresh-cut agricultural produce.